2012
DOI: 10.1016/j.apenergy.2011.11.047
|View full text |Cite
|
Sign up to set email alerts
|

Streamlined life cycle assessment of transparent silica aerogel made by supercritical drying

Abstract: This is the post-print version of the Article. The official published version can be accessed from the link below - Copyright @ 2011 ElsevierWhen developing sustainable building fabric technologies, it is essential that the energy use and CO2 burden arising from manufacture does not outweigh the respective in-use savings. This study investigates this paradigm by carrying out a streamlined life cycle assessment (LCA) of silica aerogel. This unique, nanoporous translucent insulation material has the lowest therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 16 publications
(23 reference statements)
2
50
0
5
Order By: Relevance
“…This study forms part of a wider research project focused on product development and life cycle assessment of novel retrofit technologies incorporating silica aerogel insulation (see Dowson et al 2011aDowson et al , 2011bDowson et al and 2012.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…This study forms part of a wider research project focused on product development and life cycle assessment of novel retrofit technologies incorporating silica aerogel insulation (see Dowson et al 2011aDowson et al , 2011bDowson et al and 2012.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Effective drying technologies such as supercritical fl uids drying have therefore been developed to preserve the nanoporous network of aerogels [ 3 ]. Moreover, the drying process represents the most energy intensive step during the synthesis and has a great impact on the environmental features of aerogels [ 6 ].…”
Section: Synthesis Of Aerogelsmentioning
confidence: 99%
“…Energy efficient VIPs present thin but highly effective insulation solutions, to reduce thermal losses for both new and renovated buildings [52]. The environmental impact of transparent aerogel has been assessed in study [53]. Study [50] showed that VIP had a lower environmental impact than EPS which was 42% higher than VIP, while mineral wool was only half compared to VIP.…”
Section: Roof Constructionsmentioning
confidence: 99%